THE INFLUENCE OF THE CURRICULUM ON THE DESIRE AND INTEREST OF STUDENTS TO BECOME PUBLIC ACCOUNTANTS - Dwi Satyaningrum, Elsa; Achmad Habibullah (Count : Journal of Accounting, Business and Management, 2023)
In the world of work there are alternative professions that can be done by accounting students. The curriculum is one of the factors that consider the accounting profession that will be taken from the many opportunities to take the profession. One that has great opportunities is the public accounting profession. The purpose of this study was to determine the effect of the curriculum on students' interest in becoming public accountants. The research method used is quantitative method using Independent Variables. The result of this study is that the curriculum has a direct positive effect on interest in becoming a public accountant. It can be concluded that good curriculum preparation plays an important role in attracting student interest and maintaining their motivation during the study period.